Uncovering Barcelona's Personality: Is There A Gap Between The Way The City is Presented and The Way This is Perceived by Foreigners and Locals? - Loghin, Maria M. (2011)
The focus of this research is in the field of city branding and positioning, where particular emphasis is placed on Barcelona’s reimaging years and its current identity or personality as perceived by locals and foreigners. The wish to understand this curious, yet inexplicable tendency for city policy makers and planners to try and find one landmark or a limited number of places that can visually communicate a destination’s complex ‘urban narrative’ has formed the basis for this study; the choice of topic was also guided by a personal interest to explore the extent to which the image tourists have of a city can be influenced by promotional material and the media. The research approach adopted in this dissertation includes a review of significant literature, a study of promotional material distributed by BarcelonaTurisme and the results from two surveys circulated to Barcelona’s local residents and to a wider international public. The findings show that there is a certain connection between the international perception of Barcelona and specific elements emphasized through marketing channels; and that the Departament de Turisme of the Generalitat fails to project an authentic image of Barcelona abroad that is representative of local opinions. The conclusion to be drawn from this study comes down to one fundamental idea - city authorities must begin to articulate a more collective vision by enabling residents to share their thoughts as well; in this manner, all overlapping components that form Barcelona’s diversity and uniqueness, rather than just a selected few, will be accentuated and more effectively communicated to the group of audiences targeted.